Estudo da capacidade de adsorção de metais pesados, Fe, Cu e Zn, por micropartículas de quitosana na presença de histidina - Sena, Débora do Nascimento (2017)
Alzheimer's disease (AD) is related to the anomalous binding that occurs between the β-amyloid peptide (A) and metal ions, especially the copper and zinc metals. This interaction can be facilitated if oxidative stress occurs at the brain level. One of the factors causing this stress is the presence of iron ions in this medium in large quantities. In the literature there are several studies that show that copper binds to the nucleus of βA through imidazole rings of histidine. Chelating agents, in principle pharmacologically used in the treatment of heavy metal poisoning, can be used as a chelator of these metals at a celebrale level, contributing to the treatment of AD. In this work, the chelating action of chitosan microspheres was observed, acting on the removal of copper, iron and zinc ions, in the presence of histidines (site responsible for the binding of βA to metal ions). Due to limitations in the use of βA, it was decided to use histidine, for a better understanding of the interaction that occurs in the system. Chitosan microspheres were prepared by spray-dryer for use in the adsorption of metal ions (iron, copper and zinc (monocomponents and in mixtures) with and without the presence of histidine. Isotherms and kinetic curves of adsorption were obtained, and from In the present study, it was possible to describe the interaction between chitosan and histidine, as evidenced by the decrease The adsorption isotherms showed that the presence of histidine caused a decrease in the values of Qmax For the systems containing Zn and increase of this parameter for the systems containing Cu, already for the systems Emas containing Fe the presence or not of histidine did not cause significant changes in the values of Qmax. It was also verified that in the multicomponent systems there was a decrease of the amount adsorbed in the equilibrium when compared to the monocomponent systems. From these results it is observed that chitosan presents a material potential to be used as metallic adsorbent in the presence of histidine, since even in the presence of this amino acid, chitosan continues to adsorb the metal ions, which are the potential cause of the disease.